Maternity Leave and the Rights of Pregnant Women - Ghubash, Aaesha Saeed (2017)
This research analyses the existing legal structures and policies for maternity leave and the rights of pregnant women. Comparing the UAE labour sector and country legislation departments in relation to the international policies and laws, this dissertation aims to achieve four main objectives. The first objective is to explore the ways in which the relationship between working mothers and their employers impacts on prenatal mental health conditions. The second objective is to evaluate the impacts of the UAE labour laws on Maternity Leave and Rights of Pregnant Women policies with respect to the international law and policies. The third objective is to evaluate the role the UAE anti-discrimination policies play towards the realisation of pregnant women’s rights in the workplace. Finally, the fourth objective is to provide policy recommendations on the best approach for aligning the labour laws with the rights of pregnant women and maternity leave. This research is based on interviews. The sample consists of seven individuals selected from different sectors in the UAE. The data were analysed using content analysis. Taking into consideration the data collected in this study, the key aspect of the policies and legal structures is the establishment of a sustainable relationship between employers and female employees. Employers must be ready to appreciate the fact that female employees form a critical element in their business success. In this case, they must be ready to give them proper non-discriminatory terms and conditions for maternity leave. Similarly, the UAE authorities and legislature, in particular, must institute relevant legal policies in line with the international policies to ensure that pregnant women are protected from employer’ demands and expectations that do not have clear grounds and explanation.